Rational Fabrication of Anti‐Freezing, Non‐Drying Tough Organohydrogels by One‐Pot Solvent Displacement. (27th April 2018) - Chen, Fan; Zhou, Dan; Wang, Jiahui; Li, Tianzhen; Zhou, Xiaohu; Gan, Tiansheng; Handschuh‐Wang, Stephan; Zhou, Xuechang
Abstract: Tough hydrogels, polymeric network structures with excellent mechanical properties (such as high stretchability and toughness), are emerging soft materials. Despite their remarkably mechanical features, tough hydrogels exhibit two flaws (freezing around the icing temperatures of water and drying under arid conditions). Inspired by cryoprotectants (CPAs) used in the inhibition of the icing of water in biological samples, a versatile and straightforward method is reported to fabricate extreme anti‐freezing, non‐drying CPA‐based organohydrogels with long‐term stability by partially displacing water molecules within the pre‐fabricated hydrogels. CPA‐based Ca‐alginate/polyacrylamide (PAAm) tough hydrogels were successfully fabricated with glycerol, glycol, and sorbitol. The CPA‐based organohydrogels remain unfrozen and mechanically flexible even up to −70 °C and are stable under ambient conditions or even vacuum. Abstract : Frostgeschützte, trocknungsfreie Organohydrogele wurden durch eine Solvensverdrängungsstrategie hergestellt. Wassermoleküle in den Hydrogelen werden teilweise durch Frostschutzmoleküle ersetzt, ähnlich wie bei der Kryokonservierung biologischer Proben. Die Methode ermöglicht die gezielte Einstellung der Frost‐ und Trocknungsbeständigkeit wasserbasierter Hydrogele.